Estrategias de afrontamiento y ansiedad en adultos en situación de pandemia COVID 19 - Showing Sipan, Nicolás Jorge (2022)
The Covid 19 pandemic has generated several problems in the mental health of people in the world and there are no defined answers to face this new situation. Therefore, the objective of this research is to identify which coping strategies and styles correlate with anxiety in adults in a Covid 19 pandemic situation. A systematic review method based on the PRISMA guide was used, using Scopus, APA PsycNET, Ebsco, Dialnet and SpringerLink databases, from which ten studies were selected from the years 2020 to 2022. The main findings are that the strategies that mostly increase anxiety are denial, self-blame, self-distraction, behavioral disengagement, emotional venting and substance use; and those that mostly decrease anxiety are religion, humor, positive reinterpretation and acceptance. As for styles, the problem-related coping style decreases anxiety, while the avoidant style increases anxiety; on the other hand, the emotion-related style is ambivalent in relation to anxiety, since in some cases, it reduces anxiety and in others increases it.